Spectroscopic investigation of thermo and kinetic properties for lithium-sulfur electrolytes - Abd, Suha Sahab (Edelweiss Applied Science and Technology, 2025)
The development of advanced lithium-sulfur (Li-S) batteries has gathered noteworthy attention due to their high theoretical energy density and potential for use in next-generation energy storage systems. This study focuses on the thermodynamic and dynamic analysis of advanced Li-S battery electrolytes using spectroscopic methods. By employing techniques such as nuclear magnetic resonance (NMR), Raman spectroscopy, and infrared (IR) spectroscopy, the research explores the interaction mechanisms between lithium ions and sulfur compounds within various electrolyte formulations. The results provide insights into the solvation structures, ion transport properties, and the stability of intermediates, which are significant for improving the performance and lifespan of Li-S batteries, clearing the way for the development of more efficient and durable Li-S battery systems.